The effects of teacher autonomy, student behavior and student engagement on teacher job satisfaction - Kengatharan, N. (My University, 2020)
Teacher job satisfaction has received much attention in the recent past due to its insidious effect on the quality of education and learning. By integrating self-determination theory, job demands-resource model and the theory of student involvement, the present study aims to establish the nexus of teacher autonomy, student behavior, student engagement, and teacher job satisfaction. Data were amassed with a self-administrated questionnaire from 703 teachers working in state schools. As a caveat, prior to examining the hypotheses with a partial least square based structural equation modelling approach, a confirmatory factor analysis with AMOS was performed. Results disclose that teacher autonomy and student behavior positively relate to teacher job satisfaction. The study further found that student engagement partially mediates the effect of student behavior on teacher job satisfaction. In addition, the results aver that the higher level of teacher autonomy strengthens the positive relationship between student behavior and teacher job satisfaction. The present study pushes back the frontiers of the extant literature in education and proffers many useful practical implications. The limitations and suggestions for further advancement in the field are also discussed.
Keywords: Teacher autonomy; Student behavior; Student engagement; Teacher job satisfaction; PLS-SEM approach